Strengthening universal health: development of a nursing and midwifery education quality improvement toolkit - Adelais Markaki; Jacqueline Moss; Allison Shorten; Cynthia Selleck; Lori Loan; Rhonda McLain; Rebecca Miltner; Patricia Patrician; Lisa Theus; Lilian Ferrer; Fernanda dos Santos Nogueira de Góes; Maria Teresa Valenzuela-Mujica; et al. (Universidade de São Paulo, 2019)
Objective: to present the development of a toolkit for education quality improvement in universal health and primary health care, targeting schools of nursing and midwifery in Latin American and Caribbean countries. Methods: an expert work group conducted a systematic literature review, selected key content and completed toolkit drafting, using an iterative consensus approach. International partners reviewed the toolkit. Cognitive debriefing data were analyzed, revisions and new tools were integrated, and the final version was approved. Results: twenty-two articles were identified and mapped as resources. The Model for Improvement, a data-driven approach to performance analysis, was selected for its widespread use and simplicity in carrying out the following steps: 1) organize a team, 2) assess improvement need regarding universal health and primary health care education, 3) set an aim/goal and identify priorities using a matrix, 4) establish metrics, 5) identify change, 6) carry out a series of Plan-Do-Study-Act learning cycles, and 7) sustain change. Conclusions: the Education Quality Improvement Toolkit, developed through stakeholder consensus, provides a systematic, and potentially culturally adaptable approach to improve student, faculty, and program areas associated with universal health coverage and access.